2022
DOI: 10.1111/jcpe.13615
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis prevalence in patients with ulcerative colitis and Crohn's disease ‐ PPCC: A case–control study

Abstract: Aim: The aim of this questionnaire-based case-control study was to assess whether self-reported oral health and periodontitis in patients with ulcerative colitis (UC) and Crohn's disease (CD) differ from those in matched controls without inflammatory bowel disease (IBD). Materials and Methods:A survey including questions on general anamnestic information, IBD diagnosis, and oral health was distributed online. Self-perceived overall health of teeth and gums, severe periodontitis, and tooth loss were defined as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…For example, recent observational studies on the association between IBD and periodontitis had some unmeasured or unknown potential confounding factors, such as socio-economic factors, prescription policies, and reverse causation, which were included in the limitations of their respective study (Bertl et al, 2022;Madsen et al, 2022). In this MR study, we confirmed a positive causal effect between IBD and periodontitis and a suggestive causal association between periodontitis and IBD based on large-scale GWAS summary statistics through the use of genetic instruments, which are not affected by confounders or reverse causation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, recent observational studies on the association between IBD and periodontitis had some unmeasured or unknown potential confounding factors, such as socio-economic factors, prescription policies, and reverse causation, which were included in the limitations of their respective study (Bertl et al, 2022;Madsen et al, 2022). In this MR study, we confirmed a positive causal effect between IBD and periodontitis and a suggestive causal association between periodontitis and IBD based on large-scale GWAS summary statistics through the use of genetic instruments, which are not affected by confounders or reverse causation.…”
Section: Discussionmentioning
confidence: 99%
“…However, when confounders are not observed because they are unmeasured or unknown or when the number of confounders is too large, regression methods may not provide unbiased estimates of the real association between an exposure and outcome, which may lead to some biases when interpreting the results (Sekula et al, 2016). For example, recent observational studies on the association between IBD and periodontitis had some unmeasured or unknown potential confounding factors, such as socio‐economic factors, prescription policies, and reverse causation, which were included in the limitations of their respective study (Bertl et al, 2022; Madsen et al, 2022). In this MR study, we confirmed a positive causal effect between IBD and periodontitis and a suggestive causal association between periodontitis and IBD based on large‐scale GWAS summary statistics through the use of genetic instruments, which are not affected by confounders or reverse causation.…”
Section: Discussionmentioning
confidence: 99%
“…24 In a large matched case-control study involving 1108 cases and 3429 matched controls, patients with IBD had higher odds of having worse self-perceived oral health and severe periodontitis compared to controls. 25 Another matched case-control study revealed that significantly more patients with IBD had moderate or severe periodontitis (85.6% versus 65.6%) and severe periodontitis (36.7% versus 25.6%) compared to controls. Differences were more pronounced in the 35-to 50-year-old and 51-to 65-yearold age groups, but there were no significant differences between CD and UC.…”
Section: Prevalence and Risk Of Periodontal Disease In Ibd Patientsmentioning
confidence: 99%
“…In contrast, other researchers observed higher values of plaque indices in IBD patients but no significant differences in caries and periodontal status between the study and control groups [ 20 ]. However, in the most recent studies from 2022, the authors found that the progression of periodontitis is closely associated with a worsening of the course of IBD [ 21 , 22 ]. Therefore, preventive and therapeutic strategies concerning the oral–gut axis should be imposed in IBD patients.…”
Section: Oral Health Status In Patients With Inflammatory Bowel Disea...mentioning
confidence: 99%